2017
DOI: 10.1007/s00383-017-4103-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of retained Port-A-Cath fragments during removal

Abstract: Port-A-Caths that are retained after attempted removal is a complication encountered predominantly in catheters that have been in use for a prolonged duration. Furthermore, factor replacement therapy in haemophiliacs may be a risk factor for this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…No additional treatment was offered because the patient remained asymptomatic [4]. This is consistent with the findings of Aworanti et al that suggested that chronic use of CVC is a common factor when retained catheters are encountered [1]. In this study, out of 174 pediatric CVC insertions and 135 subsequent removals, three patients (2.2%) failed removal; all three patients had had their CVC for greater than six years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…No additional treatment was offered because the patient remained asymptomatic [4]. This is consistent with the findings of Aworanti et al that suggested that chronic use of CVC is a common factor when retained catheters are encountered [1]. In this study, out of 174 pediatric CVC insertions and 135 subsequent removals, three patients (2.2%) failed removal; all three patients had had their CVC for greater than six years.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the CVC erosion into the intima caused an inflammatory response that created a calcified “cast” within the vessel wall. The mechanism behind CVC retention is likely linked to this calcified “cast.” According to Aworanti et al, the typical fibrin sheath that develops around a catheter can undergo epithelialization, calcification, and then adhere to the tunica intima of the vein wall [1]. While vascular calcifications typically occur in arteries, a central vein calcification is rare but has been described [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of stuck catheters is not exactly known, and different results have been reported with an incidence ranged from 0.3 to 2.2% [21]. The long duration of the catheter was the main predisposing factor to this complication [22,23]. To facilitate removal, a second incision was required in 4 patients and venotomy in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The vasculature around the indwelling catheter can be distorted with collaterals impinging on arterial vessels [25] . This makes port-a-caths difficult to remove, and fragments are often retained in the central vein following an attempt at removal [26] .…”
Section: Discussionmentioning
confidence: 99%